Pathways to Reducing Poverty and Sharing Prosperity in India : Lessons from the Last Two Decades - Chatterjee, Urmila; Murgai, Rinku; Narayan, Ambar; Rama, Martin (World Bank, Washington, DC, 2016)
India is uniquely placed to help reduce global poverty and boost prosperity. The country has the largest number of poor people in the world, as well are the largest number of people who have recently escaped poverty. There is an emerging middle class but the majority of people are still vulnerable to falling back into poverty. What lessons do the past two decades offer for what it will take for the country to sustain progress and bring about deeper changes? This synthesis brings together the key insights from extensive and in-depth research conducted by the World Bank on India’s experience in reducing poverty and sharing prosperity over the last two decades. The beginning chapter of the synthesis offers an overview of the trends in living standards and mobility in India. This is followed by a chapter on the main drivers of poverty reduction. The third chapter sheds light on some of the gaps India needs to fill for sustaining mobility and spreading prosperity more widely.